Executive Function: Cognition and Behaviour in Adults with Autism Spectrum Disorders (ASD). - Johnston, Kate; Murray, Kim; Spain, Debbie; Walker, Ian; Russell, Ailsa (Journal of Autism & Developmental Disorders, 2019)
Studies of executive function (EF) in autism spectrum disorder (ASD) have reported mixed findings. Possible confounds include EF domain assessed and co-occurring neurodevelopmental diagnoses. EF task performance across multiple domains and everyday function of autistic adults (n = 110) was significantly different to age- and IQ-matched controls (n = 31). Although significantly more likely to fall into the clinically impaired range, 35.8% of the ASD group showed no impairment on EF measures. Factor analysis revealed a single unifying EF construct rather than a selective pattern of impairment. Dysexecutive behaviours were frequently reported in the ASD group, unrelated to Autism symptoms, EF task performance or co-occurring conditions. This study suggests autistic adults can experience clinically significant executive function difficulties and co-occuring dysexecutive behaviours that are disabling in everyday life.